Pengaruh Minat Belajar Matematika Terhadap Kemampuan Penalaran Matematik Siswa SMP - Gida Kadarisma; Tina Rosyana; Adi Nurjaman (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2019)
Mathematics is often perceived as a difficult subject, therefore students' interest in learning in mathematics is relatively low. This results in low student learning outcomes, whereas in mathematics there is an important ability possessed by students, namely mathematical reasoning abilities that enter into the High Order Thinking Skill, based on that the purpose of this study is to analyze the influence of learning interest on students' mathematical reasoning abilities. The method in this study is a correlational method to see the effect of a variable on other variables, with a population of eighth grade students of SMPN 3 Ngamprah with samples taken in one class. The instrument of this study was a 5-item test instrument to measure reasoning ability and a non-test questionnaire in the form of 40 statements used to measure interest in learning in mathematics. From the results of data analysis, it can be concluded that there is a significant positive influence between learning interest with mathematical reasoning ability, and the correlation coefficient of 0.88, which means the relationship between interest in learning mathematics and mathematical reasoning ability is classified as very strong. Therefore, in bringing learning the teacher should make learning that can increase student interest in learning so that students' mathematical reasoning abilities increase